Increasing Mortality Burden among Adults with Complex Congenital Heart Disease. (7th July 2014) - Greutmann, Matthias; Tobler, Daniel; Kovacs, Adrienne H.; Greutmann‐Yantiri, Mehtap; Haile, Sarah R.; Held, Leonhard; Ivanov, Joan; Williams, William G.; Oechslin, Erwin N.; Silversides, Candice K.; Colman, Jack M.
Abstract Background Progress in management of congenital heart disease has shifted mortality largely to adulthood. However, adult survivors with complex congenital heart disease are not cured and remain at risk of premature death as young adults. Thus, our aim was to describe the evolution and mortality risk of adult patient cohorts with complex congenital heart disease. Methods Among 12 644 adults with congenital heart disease followed at a single center from 1980 to 2009, 176 had Eisenmenger syndrome, 76 had unrepaired cyanotic defects, 221 had atrial switch operations for transposition of the great arteries, 158 had congenitally corrected transposition of the great arteries, 227 had Fontan palliation, and 789 had repaired tetralogy of Fallot. We depict the 30‐year evolution of these 6 patient cohorts, analyze survival probabilities in adulthood, and predict future number of deaths through 2029. Results Since 1980, there has been a steady increase in numbers of patients followed, except in cohorts with Eisenmenger syndrome and unrepaired cyanotic defects. Between 1980 and 2009, 308 patients in the study cohorts (19%) died. At the end of 2009, 85% of survivors were younger than 50 years. Survival estimates for all cohorts were markedly lower than for the general population, with important differences between cohorts. Over the upcoming two decades, we predict a substantial increase in numbers of deaths among young adults with subaortic right ventricles, Fontan palliation, and repaired tetralogy of Fallot. Conclusions Anticipatory action is needed to prepare clinical services for increasing numbers of young adults at risk of dying from complex congenital heart disease.